Designing A Multi-item Product Inventory Policy to Reduce Stockouts on CV VLJ - Fransiska Hernina Puspitasari; V. Reza Bayu Kurniawan; Trisna Yulianti (Universitas Islam Raden Rahmat, Malang, 2024)
Managing inventory to be able to meet consumer orders is crucial. However, often the ordered goods are not available because the quantity ordered is less so the inventory in the warehouse is out-of-stock. The determination of the order quantity or period is often only based on intuition. This causes lost sales. CV VLJ experienced a similar thing that caused consumers to buy unavailable items to other stores. Therefore, this study aims to reduce these lost sales and minimize the total inventory costs incurred. The determination of the order quantity or period is calculated using the Q and P models along with the calculation of lost sales and total costs for all SKUs sold. Based on the results of inventory simulations, cost reductions of lost sales of 88-99% and total cost in average of 33% can be achieved compared to the actual condition.